EVEKTIFITAS METODE DRILLS FOR GAME – LIKE SITUATION TERHADAP KEMAMPUAN PASSING BAWAH ATLET BOLAVOLI - Alfiqroam Kumar; Riyan Febriyanto; Ali Mardius (Jurnal Muara Olahraga, 2022)
Abstract: The purpose of this study was to see the effect of the Drills For Game – Like Situation exercise on the lower passing technique skills of volleyball extracurricular students at SMA Negeri 1 Sutera. This type of research is an experiment (quasi experiment) which aims to see the effect of treatment on variables. The treatment in this study is the Drills For Game – Like Situation exercise. The population in this study amounted to 18 people. The sampling technique uses total sampling. Thus the number of samples in this study were 18 Volleyball extracurricular students at SMA Negeri 1 Sutera. The data analysis technique used is t test analysis (mean difference test) with a significant level α = 0.05. The results of the study obtained that the average pre-test score was 6 and the average score after the post-test was 12. Based on the t test, the value of tcount = 14.312> ttable = 2.10, with a confidence level of α = 0.05. The results showed that there was a significant effect of the Drills For Game – Like Situation training method on the ability of the underhand passing technique of volleyball extracurricular students at SMA Negeri 1 Sutera. This means that one of the training methods, namely Drills For Game – Like Situation, can be used to influence the ability of volleyball underhand passing techniques. Keywords: Drills For Game – Like Situation, Technical Ability to Pass Under Volleyball